THE EMERGENCE OF WRITING IN ANCIENT GREECE - Salohiddinov Bunyod (Ustozlar uchun, 2023)
Abstract: This article presents information about the origin, formation and change of the Greek script. In addition, it was analyzed that the basis for the creation of Greek literature and the wide distribution of written sources in the study of history based on the Greek script.